2020
DOI: 10.3390/su12083285
|View full text |Cite
|
Sign up to set email alerts
|

The Bike-Sharing System as an Element of Enhancing Sustainable Mobility—A Case Study based on a City in Poland

Abstract: The bike-sharing system allows urban residents to rent a bike at one of the rental stations located in the city, use them for their journey, and return them to any other or the same station. In recent years, in many cities around the world, such systems were established to encourage their residents to use bikes as an element of enhancing sustainable mobility and as a good complement to travel made using other modes of transport. The main purpose of this article is to present the results of an analysis of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 75 publications
0
48
0
1
Order By: Relevance
“…Wireless charging electric trams can be powered remotely from wireless charging infrastructure on the railway and can store the remaining electricity in the battery. Macioszek et al [7] indicated that the bicycle sharing system is an effective tool to also need further exploration. Hence, from the perspective of improving subway operation safety, identifying and quantifying the effect of the safety climate on safety behavior is of great significance due to practical necessity.…”
Section: Introductionmentioning
confidence: 99%
“…Wireless charging electric trams can be powered remotely from wireless charging infrastructure on the railway and can store the remaining electricity in the battery. Macioszek et al [7] indicated that the bicycle sharing system is an effective tool to also need further exploration. Hence, from the perspective of improving subway operation safety, identifying and quantifying the effect of the safety climate on safety behavior is of great significance due to practical necessity.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we split our test set into sequences with simple and complex tracking situations based on the amount of VRUs present in the scene and the degree of tracking ambiguity caused by occlusion. The "simple" sub-set consists of the sequences (1, 2,3,7,8,9,10,11,12,13) with 1150 frames and 1479 VRUs, while the "complex" sub-set consists of the remaining 6 sequences with 690 frames and 3509 VRUs. From the data visualized on Figure 9 we can conclude that all trackers perform significantly better in simple tracking situations than in complex ones which is also indicated by better object detection at the input.…”
Section: Multi-object Trackingmentioning
confidence: 99%
“…Increasing the use of PT is one of the most convenient strategies to alleviate the excessive use of private cars in most metropolitan areas, as introduced by Eboli et al (2015) [1]. There are different forms of sustainable PT in our normal daily lives, such as buses [2], trams [3], subways [4], public bicycles [5], etc. With the rapid progress of transportation technologies, there are increasingly more advanced applications involved in comprehensive PT systems, such as maglev trains [6], high-speed rails [7], electric vehicles [8], driverless vehicles [9], customized vehicles [10], etc.…”
Section: Public Transportationmentioning
confidence: 99%
“…In the sample, the passenger had a rest during the trip, and his energy recovered to some extent, which is worth 5 t m −t 1 units of value per time and 5 units of value in total during the time period t 1 ∼ t m for the energy factor. At the same time, the taxi driver kept driving during the trip, and his energy has declined to some extent, which is worth 5 t m −t 1 unit value per time and 5 units of value in total during the time period t 1 ∼ t m in the energy factor. Moreover, taxi energy has declined much to support the transportation process, which is worth 50 t m −t 1 units of value per time and 50 units of value in total during the time period t 1 ∼ t m for the energy factor.…”
mentioning
confidence: 99%